1998
DOI: 10.1103/physrevlett.80.2389
|View full text |Cite
|
Sign up to set email alerts
|

First-PrinciplesT-Matrix Theory with Application to the 6 eV Satellite in Ni

Abstract: In photoemission spectra of strongly correlated systems one usually observes a satellite structure below the main peak. Description of such satellite structures in the commonly used GW approximation has been found to be insufficient. To account for these satellite structures that originate from shortrange correlations, we have developed a T -matrix formalism for performing ab initio calculations on real systems. The method is applied to Ni and we obtain a satellite structure below the Fermi level as well as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 22 publications
1
85
0
2
Order By: Relevance
“…Other methods for including strong correlations, such as the Hubbard model, Hubbard plus GW , or T −matrix methods have been used in calculations of XAS and XPS, and could be adapted for calculations of RIXS as well. 45,46 Yet another approach for including strong correlations relevant to this discussion is multi-configurational multiple-scattering theory. 47 This method has already been used to account for mixing of the core-holes in XAS, and could be extended to calculations of RIXS.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods for including strong correlations, such as the Hubbard model, Hubbard plus GW , or T −matrix methods have been used in calculations of XAS and XPS, and could be adapted for calculations of RIXS as well. 45,46 Yet another approach for including strong correlations relevant to this discussion is multi-configurational multiple-scattering theory. 47 This method has already been used to account for mixing of the core-holes in XAS, and could be extended to calculations of RIXS.…”
Section: Discussionmentioning
confidence: 99%
“…20 The calculations by Zhukov et al 18 and Bacelar et al 19 showed that the evaluated lifetimes also strongly vary along the 4d-series following trends in electronic structure. The extension, GW + T , of the GW approximation by inclusion of multiple electron-hole scattering within a T-matrix approximation 21,22,23,24,25 results in the decrease of the GW lifetime value that brings theory and experiment to better agreement. 12,24,25 In this paper we perform TR-2PPE measurements of excited electron lifetimes in Mo and Rh and compare these results with the GW and GW + T calculated lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…One can then generate particle number conserving approximations when combining many-body methods, such as GW + T-matrix [42] and the FLEX approximation [43,44], provided that each diagram is consistently dressed.…”
Section: Number Conservationmentioning
confidence: 99%